The Influence of Interfering Substances on the Antimicrobial Activity of Selected Quaternary Ammonium Compounds - Paula A. Araújo; Madalena Lemos; Filipe Mergulhão; Luís Melo; Manuel Simões (International Journal of Food Science)
Standard cleaning processes may not remove all the soiling typically found in food industry, such as carbohydrates, fats, or proteins. Contaminants have a high impact in disinfection as their presence may reduce the activity of disinfectants. The influence of alginic acid, bovine serum albumin, yeast extract, and humic acids was assessed on the antimicrobial activities of benzalkonium chloride and cetyltrimethyl ammonium bromide against Bacillus cereus vegetative cells and Pseudomonas fluorescens. The bacteria (single and consortium) were exposed to surfactants (single and combined) in the absence and presence of potential disinfection interfering substances. The antimicrobial effects of the surfactants were assessed based on the bacterial respiratory activity measured by oxygen uptake rate due to glucose oxidation. The tested surfactants were efficient against both bacteria (single and consortium) with minimum bactericidal concentrations ranging from 3 to 35 mg·L−1. The strongest effect was caused by humic acids that severely quenched antimicrobial action, increasing the minimum bactericidal concentration of the surfactants on P. fluorescens and the consortium. The inclusion of the other interfering substances resulted in mild interferences in the antibacterial activity. This study clearly demonstrates that humic acids should be considered as an antimicrobial interfering substance in the development of disinfection strategies.